Pelatihan Penguatan Kelembagaan Ekonomi Kelurahan Melalui Pelatihan Manajemen Usaha dan Pencatatan Keuangan Dasar Di Kota Balikpapan - Pudjiati Pudjiati; Endah Lestari; Henny Okta Piyani; Andi Hilda Yani (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This community service activity aims to strengthen village economic institutions, particularly Village-Owned Enterprises (BUMKel) operating in Balikpapan City, one of which is the Merah Putih Cooperative. Strengthening is carried out through business management training and basic financial recording that is applicable and easy to implement by business managers at the village level. The problems faced by village economic institutions, especially the Merah Putih Cooperative, such as a lack of understanding in preparing business plans, unsystematic financial management, and minimal human resource capacity in managing financial reports, are the background to the importance of this activity. With the training designed in a participatory manner, it is expected that participants will be able to understand the basic principles of business management (planning, organizing, implementation, and evaluation) and be able to apply a simple financial recording system based on Excel or a standardized manual format. This activity is carried out in the form of workshops, interactive discussions, and direct practice in preparing business financial reports. The main targets of this activity are the administrators and members of the Merah Putih Cooperative, as well as village officials involved in community economic development. The expected results of this activity are increased management capacity in designing and managing business units, as well as the availability of routine and accountable business financial reports, which can ultimately increase the sustainability and independence of the Merah Putih Cooperative.